Negatywne przejawy konkurencji w agrobiznesie - Woźniak, Leszek; Ziółkowski, Bożydar; Dziedzic, Sylwia (Negative Symptoms of Competitiveness in Agribusiness, 2006)
The aim of this paper is to present some factors which decide about a need to make more rational competitiveness in agribusiness. The given examples of existing solutions argue that the important think is to diminish negative impact on environment in the local, regional and global aspect. This approach is relevantly closely connected with the care about life conditions of next generations.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 515-522